The The Hybrid Space in Santa Maria (RS): Experiencing the city as a Pokémon Go player (Terr@ Plural, 2022)
We studied the smartphone’s game, Pokémon Go, from the perspective of phenomenology and the player's experience The experience constitutes and is constituted by the concept of hybrid space, given by the presence and movement of the player in the ‘real’ and’ ‘virtual’ spaces. We operationalized the search through self-narratives produced by the main author of the articleI in his actions as a player in the urban space of Santa Maria (RS). As a result, we verified that there is a crucial importance of the body and movement for the production of the experience and that the hybrid space, conformed in the practice of playing, expands the network of meanings of the urban space. In addition, we note a relationship between the practice of Pokémon Go and the concept of ‘geograficity’, which we call ‘hybrid geograficity’.
Keywords: Digital games; Phenomenology; Real Space; Virtual Space; Self-narratives